Long-term sustainability of a physical activity and nutrition intervention for rural adults with or at risk of metabolic syndrome. - Jancey, Jonine; Lee, Andy H; James, Anthony P; Howat, Peter; Hills, Andrew P; Anderson, Annie S; Tran, Van Dinh; Blackford, Krysten (2020)
OBJECTIVE: To determine longer-term (18-month) sustainability of a six-month physical activity and nutrition intervention for 50-69-year-olds with or at risk of metabolic syndrome residing in a rural Australian community.